Fair ways to share benefits from community forests? How commodification is associated with reduced preference for equality and poverty alleviation. (22nd May 2019) - Martin, Adrian; Kebede, Bereket; Gross-Camp, Nicole; He, Jun; Inturias, Mirna; Rodríguez, Iokiñe
Abstract: This research is concerned with the trend towards commodification of forestry, in the context of community forest governance for sustainable development in the tropics. In these contexts, commodification takes different forms, including sales of certified timbers and sales of carbon credits. In addition to the general aim to enhance income, these market-based forestry interventions typically aim to align with sustainable development agendas, including (a) safeguarding ecological integrity and (b) promoting poverty alleviation. Our concern here is that the process of forest commodification might lead to a shift in local norms of benefit-sharing, in ways that can hinder these key components of sustainable development goals. We report the results of a survey ( N = 519) conducted across sites in Bolivia, China and Tanzania that shows that switching from non-monetary to monetary benefits is associated with changes in preferences for distributional fairness in ways that may be detrimental to the poor. In particular, we show that forest commodification is associated with a lower likelihood of selecting pro-poor or egalitarian approaches to benefit sharing and higher likelihood of selecting to distribute benefits in a way that rewards individual contributions or compensates losses.